Mind-Body Interactions in Anxiety and Somatic Symptoms. Issue 1 (January 2016) - Mallorquí-Bagué, Núria; Bulbena, Antonio; Pailhez, Guillem; Garfinkel, Sarah N.; Critchley, Hugo D.
Abstract : Abstract: Anxiety and somatic symptoms have a high prevalence in the general population. A mechanistic understanding of how different factors contribute to the development and maintenance of these symptoms, which are highly associated with anxiety disorders, is crucial to optimize treatments. In this article, we review recent literature on this topic and present a redefined model of mind-body interaction in anxiety and somatic symptoms, with an emphasis on both bottom-up and top-down processes. Consideration is given to the role played in this interaction by predisposing physiological and psychological traits (e.g., interoception, anxiety sensitivity, and trait anxiety) and to the levels at which mindfulness approaches may exert a therapeutic benefit. The proposed model of mind-body interaction in anxiety and somatic symptoms is appraised in the context of joint hypermobility syndrome, a constitutional variant associated with autonomic abnormalities and vulnerability to anxiety disorders.